PENGARUH PENGGUNAAN MEDIA KINCIR AIR TERHADAP HASIL BELAJAR PESERTA DIDIK PADA PEMBELAJARAN IPAS KELAS IV SDIT LUKMANUL HAKIM KABUPATEN GORONTALO - Putri Anggreani Silsilia A. Husuna; Lian G. Otaya; Ingka Rizkiyani Akolo (Al-mujahidah, 2026)
This study aims to determine the effect of the use of waterwheel media on student learning outcomes in science learning for Grade IV of SDIT Lukmanul Hakim, Gorontalo Regency. The type of research conducted by the researcher is quantitative experimental research. The population in this study were all 26 students of grade IV of SDIT Lukmanul Hakim. Based on the results of research conducted on grade IV students of SDIT Lukmanul Hakim using the One Group Pretest-Posttest design. The results of statistical analysis through the Wilcoxon test showed an Asymp. Sig (2-tailed) value <0.05, so empirically it can be ascertained that there is a significant difference between learning outcomes before and after the use of waterwheel media. These findings indicate that the use of waterwheel media has a positive and significant effect on student learning outcomes, because this media is able to provide concrete learning experiences, facilitate understanding of concepts, and increase student active involvement during learning. Thus, all research results as a whole answer the problem formulation that the use of waterwheel media does have an effect on improving student learning outcomes in science learning on the material of changes in energy forms.